Markets for Tradeable CO2 Emission Quotas Principles and Practice - Chichilnisky, Graciela (OECD Economics Department Working Papers, 1995)
This paper reviews a range of issues relating to tradeable carbon dioxide quotas. It considers the economic principles on which they are based, compares them with alternative carbon abatement policies, and reviews many aspects of how tradeable quotas would be implemented in practice ...